HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN PELAKSANAAN TOILET TRAINING PADA ANAK USIA TODDLER (1-3 TAHUN) DI KECAMATAN SEI SIKAMBING B MEDAN - Mardhiah; Suherni; Bintang Hartati; NindaWahyuni (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
According to the 2021 National Household Health Survey (SKRT), in Indonesia it is estimated that the number of toddlers who have difficulty controlling their bowel movements and urination at the age of toddlers reaches 75 million children. This study aims to determine the relationship between the level of maternal knowledge and the implementation of toilet training in toddlers (1-3 years) in Sei Sikambing B Village, Medan. The research method uses descriptive correlation with a cross-sectional approach. The sample in this study were mothers who have toddlers (1-3 years) with a total of 48 respondents and samples were taken using the Slovin formula